Division Or Integration of Labor: Exploring Course Experiences of Four L2 Students in Separated and Integrated Undergraduate Composition Courses - Yacoub, Mohamed (JEES (Journal of English Educators Society), 2025)
This study explores the narrated experiences of four L2 students enrolled in required undergraduate composition courses, ENG 101 and ENG 202. It pursues two primary purposes: first, to enrich and deepen our understanding of the participants’ narratives; and second, to draw upon these narratives to develop pedagogical implications for writing program administrators regarding the two major structures of First Year Composition (FYC) programs; integration and separation. Conducted at public university in the northeastern United States, the study employed a narrative research methodology, in which the four participants were interviewed and asked to share study materials and artifacts. The findings are presented through five salientthemes that reflect the participants’ experiences in ENG 101 and ENG 202. These themes are: 1) factors influencing the participants’ section selection, 2) L1 classmates as both a resource and a challenge, 3) the impact of section type on student engagement, 4) how participants’ perception of the curriculum influencedtheir performance, and 5) the negotiation of student identity. The study concludes that writing programs should not impose a single structure on L2 students but should offer both options, thereby supporting students’ agency in making informed choices. HIGHLIGHTS: Offering Both Integrated and Separated Sections Supports Student Agency: The study found that L2 students benefit when they are given the choice between multilingual (separated) and mainstream (integrated) composition courses, as this supports their confidence, academic needs, and personal growth. L1 Classmates Are Both a Resource and a Challenge for L2 Students: While some L2 students feel intimidated by native speakers and engage less in integrated classes, others see American classmates as valuable for improving their English skills and learning about local culture. Curriculum and Engagement Are Shaped by Section Type: Participants’ perceptions of reading materials, writing assignments, and classroom discussions varied depending on whether they were in integrated or separated sections, with integrated sections offering more opportunities for cultural exchange but also presenting greater challenges for active participation.